(untitled) (Altre Modernità, 2014)
The Kokuryûkai was founded in 1901 to foster the outbreak of a Russo-Japanese War. For these sake, the members of the society started spying in Korea, Manchuria, China and even Russia and prepared the image of a despotic and weak country, which would not be able to counter Japanese aspirations on the Asian mainland anymore. In 1895 the Triple Intervention under Russian leadership had finished the Japanese dreams of getting the Liaodong peninsula as a compensation for the Sino-Japanese War. And just some years later as a consequence of the Boxer Rebellion Russia seized Manchuria and was not willing to negotiate about its abandonment. Finally, the Japanese nationalists saw no alternative than founding another secret society to prepare the Japanese army and public for war. Due to this, information about the possible opponent needed to be collected and an anti-Russian propaganda campaign was started by the members. This made Russia the enemy number one and many publications like Uchida Ryôhei’s Roshiaron started to provide a negative image of the future enemy on the battlefield for Asian hegemony. An article will outline the establishment of this anti-Russian image by analyzing the measures of the Kokuryûkai members from its foundation until the outbreak of the Russo-Japanese War in 1904.